Loadbearing capacity and safety for winter roads improvement reinforcement and ice modification - G. Y. Goncharova; V. V. Sirotiuk; O. V. Yakimenko; P. V. Orlov; R. E. Dolgodvorov (Вестник СибАДИ, 2024)
Introduction. The natural processes associated with the thawing of permafrost and the accompanying risks of man-made disasters have been steadily increasing in recent years. At the same time, a new space of opportunities opens up for the development of territories, the formation of new cargo transportation routes, both in transit and directly to the Arctic regions. The number of consumers is increasing, the requirements for the economic efficiency of transport infrastructure and the requirements for materials for its construction and maintenance are increasing.Materials and methods. Water ice is one of the most widespread substances in the northern nature, and the experience of its use as a building material goes back centuries. At the same time, the use of water ice still has no alternative in the construction of seasonal ice roads and crossings, including for solving the tasks of oil and gas companies. This article is devoted to the possibilities of using modern materials that change the properties of water ice and structural and technological solutions to increase the carrying capacity and safety of ice crossings and extend the service life of winter trucks.Results. Experimental and theoretical studies, tests at the landfill, pilot production tests at ice crossings have shown the possibility to significantly increase the carrying capacity and safety of the transport when reinforcing ice. The introduction of water ice modifiers together with its reinforcement significantly improve the physical and mechanical properties of water ice.Conclusion. The authors’ idea of the possibilities of a significant increase in the bearing capacity of the ice cover on winter roads, traffic safety, prolongation of their service life with the combined use of special reinforcing materials and chemical modifiers of water ice is presented. The reasons for the limited use of the recommendations proposed by the authors are disclosed.